Toward Excellence of Transition Metal‐Based Catalysts for CO2 Electrochemical Reduction: An Overview of Strategies and Rationales. Issue 7 (16th April 2020) - Li, Mengran; Garg, Sahil; Chang, Xiaoxia; Ge, Lei; Li, Liye; Konarova, Muxina; Rufford, Thomas E.; Rudolph, Victor; Wang, Geoff
Abstract: Rational modulations of interactions between the catalyst surface and intermediates are challenging but extremely important to achieve an efficient and selective electrochemical CO2 reduction (CO2 R). Current CO2 R catalyst design remains inefficient because of a gap between existing practical design paradigms and theoretical studies in catalysis. This review attempts to mitigate this gap through a critical discussion of the correlations between recent strategies to develop transition metal‐based catalysts and the underlying rationales and mechanisms. These strategies include surface engineering, the introduction of heterogeneous atoms, and dimension control, and can be implemented by tactics such as controlling catalyst surface facets, surface tethering, alloying, inducing strains, oxide derivation, molecular scaffolding, and nanostructuring. How these tactics are able to tailor the electronic structure, adsorption geometry, density of active sites, and local environment of catalyst to achieve an efficient and selective CO2 R is described. This review concludes with a discussion of the key research needs in this field such as the surface proton formation and transfer involved in CO2 R, the roles of mass‐transfer or electrode kinetics in CO2 R catalysis, development of robust, standardized catalyst testing protocols, and application of machine learning and high‐throughput experiment to accelerate catalyst screening processes. Abstract : This review attempts to link the practical catalyst development strategies with the theoretical understanding of the transition metal catalysis for CO2 electrochemical reduction. Modulation of electronic structures of the metal surface and reaction intermediate adsorption geometries are at the core of vast catalyst design tactics, which can be mainly manipulated by the catalyst compositions and surface atomic interdistances.